Drag force on two disks moving in a granular bed. (September 2016) - Kuwabara, A; Yoshioka, N; Shimada, T; Ito, N
Abstract: The drag forces acting on a disk and two disks dragged at constant speeds in a two-dimensional granular bed are measured by an event-driven molecular dynamics simulation. The normal drag force on a disk in case of two disks are dragged in parallel, F2x, is almost the same with the drag force on a disk in case of a single disk is dragged, F1x, when they are apart enough. As the distance between the disks D decreases, F2x increases until it has the maximum at a certain point, D*, and after that it decreases. When D is small enough, whether F2x is larger than F1x or not depends on the ratio of the average radius of the granular prticles to the one of the dragged objects.